E-Dagang di Malaysia: Perkembangan, Perlaksanaan, dan Cabaran (Sains Humanika, 2011)
The usage of e-commerce is rapidly expanding around the world. Through this development, it has led to a more positive and stronger sectors of economy. In Malaysia, the development of Information and Communication Technology (ICT), especially the Internet has enabled people in Malaysia to use e-commerce in their business and daily activities. E-commerce applications are growing rapidly among the users and it is not just limited to business. In fact, it can also provide with many advantages to its consumer to carry out the financial transactions anywhere and anytime. This article discusses the scope of e-commerce applications in terms of ongoing financial developments especially in Malaysia. In addition, the researchers also discuss on how the implementation of e-commerce application, particularly in sectors related to ecommerce. Furthermore, it also concerned with the challenges faced by the consumers in using the e-commerce applications in their daily lives optimistically. This article then discusses further on the argument of the previous studies with reference to the e-commerce in terms of chronological development in Malaysia.
Keywords: E-commerce; development; implementation; challenges; Malaysia